Sistem Pakar Diagnosa Penyakit Pada Sapi Berbasis Android - Ari Negara, I Komang Agus; Muliantara, Agus (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022, 2022)
Cows are livestock that are widely kept by people in Indonesia. Like other livestock, cows can also get disease. Currently, the disease that is rife in attacking cows is Mouth and Nail Disease (FMD). The spread of this disease can be harmful to livestock production, so it is important to know early on the disease that occurs in cattle. This study aims to build a system that can be used to diagnose diseases to minimize the spread of FMD. The system built applies an expert system in diagnosing disease with the method of determining disease using the forward chaining method. The system built is implemented on an Android basis considering that currently the use of mobile-based devices has been widely used. The results of this study indicate that the expert system with the forward chaining method can be applied and functions well on an android basis.